Composite decolorizing agent for industrial wastewater and preparation method of composite decolorizing agent
By using a composite decolorizing agent, which consists of composite polyolefin, ferric chloride solution and polyacrylamide, combined with activated chitosan and multi-core hydroxy iron complex, the problem of insufficient decolorization and COD removal rate of the printing and dyeing industry wastewater in the prior art is solved, and efficient wastewater treatment effect is achieved.
Patent Information
- Application Number
- CN202510149454.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, when treating the printing and dyeing industry wastewater, the decolorization and COD removal rates need to be improved, and common technologies have problems such as difficulty in regeneration of adsorbents, high operating costs, and membrane pollution.
A composite decolorizer is used, which consists of composite polyolefin, ferric chloride solution and polyacrylamide. By activating chitosan, a multi-dimensional crosslinking structure is formed, and a multi-core hydroxy iron complex of ferric chloride solution is combined to achieve efficient adsorption and flocculation and settlement of color substances and organic matter in the printing and dyeing wastewater.
It significantly improves the decolorization rate and COD removal rate of the printing and dyeing industry wastewater, improves the adsorption capacity and flocculation and settlement efficiency, and reduces the treatment cost.
Smart Images

Figure SMS_1 
Figure SMS_7 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of decolorizing material processing, and in particular to a composite decolorizing agent for industrial waste water and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry, the types and quantity of industrial wastewater have increased rapidly, and the pollution of water bodies has become increasingly widespread and serious, posing a serious threat to human health and safety. Printing and dyeing industrial wastewater usually has the characteristics of high chroma, high COD (chemical oxygen demand), high BOD5 (biochemical oxygen demand five days), and contains a large amount of difficult-to-degrade organic matter and toxic and harmful substances. These characteristics make the treatment of printing and dyeing wastewater a major problem in the field of environmental protection;
[0003] At present, the commonly used technologies for decolorization of printing and dyeing wastewater mainly include adsorption, coagulation, oxidation, membrane separation and biological methods. However, these technologies all have certain limitations in practical applications. For example, although the adsorption method has a good decolorization effect, the adsorbent is difficult to regenerate and the treatment cost is high. Although the coagulation method is simple to operate, its decolorization effect is not ideal for certain types of dye wastewater. Although the oxidation method can destroy the chromophore of the dye molecule, the required oxidant is expensive and may cause secondary pollution. Although the membrane separation method has a high treatment efficiency, membrane pollution and membrane cost issues limit its wide application. The biological method has limited treatment effect due to the presence of difficult-to-degrade organic matter and toxic and harmful substances in printing and dyeing wastewater.
[0004] Prior art, the invention patent with publication number CN101596444A, discloses a highly efficient decolorizing agent for industrial wastewater and its preparation method, which is prepared from sepiolite and flocculant, and can be used together with a coagulant aid, wherein the flocculant is polyaluminum chloride or aluminum sulfate or aluminum chloride, and the coagulant aid is polyacrylamide. The agent has the advantages of good decolorizing effect, fast flocculation and precipitation speed, reliable performance and simple operation.
[0005] However, it mainly uses the adsorption effect of sepiolite and the flocculation and sedimentation effect of flocculants to decolorize the material and reduce COD. The adsorption effect of a single material is limited to the adsorption effect on color molecules. In addition, sepiolite material, as an inorganic particle, is easy to settle quickly during use, resulting in its removal effect on color molecules, organic matter and suspended matter in industrial wastewater needs to be further improved.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The object of the present invention is to provide a composite decolorizing agent for industrial wastewater and a preparation method thereof, so as to solve the technical problem that the decolorizing agent in the prior art for printing and dyeing industrial wastewater and the COD removal rate need to be further improved.
[0008] The object of the present invention can be achieved by the following technical scheme: A composite decolorizing agent for industrial wastewater, comprising the following components in parts by weight: 70-80 parts of composite polyolefin, 25-30 parts of ferric chloride solution, and 3-5 parts of polyacrylamide;
[0009] The preparation method of the composite polyolefin is as follows: composite chitosan, acryloyloxyethyl trimethyl ammonium chloride, fumaric acid and deionized water are mixed, the temperature of the reaction system is increased to 70-80° C., an initiator solution is added dropwise to the reaction system, and the reaction is carried out by heat preservation for 5-6 hours to obtain the composite polyolefin.
[0010] The synthetic reaction mechanism of composite polyolefin is:
[0011] In the reaction process, deionized water is used as a solvent. Under the action of an initiator, free radical addition reaction occurs on the unsaturated double bonds of acryloyloxyethyltrimethylammonium chloride and fumaric acid molecules to form a polyolefin coating on the composite chitosan molecules, thereby preparing a composite polyolefin.
[0012] Furthermore, the amount ratio of the composite chitosan, acryloyloxyethyltrimethylammonium chloride, fumaric acid, deionized water and initiator solution is 4g:5g:2g:30mL:5mL, and the initiator solution is composed of azobisisobutyronitrile and deionized water at 1g:10mL.
[0013] Furthermore, the preparation method of the composite chitosan is as follows: 3-amino-4-hydroxybutyronitrile, activated chitosan and ammonium chloride solution are mixed and stirred, the temperature of the reaction system is increased to 28-32°C, formaldehyde solution is added dropwise to the reaction system, the reaction temperature is controlled not to be higher than 65°C, after the addition is completed, aluminum chloride is added to the reaction system, the temperature of the reaction system is increased to 70-80°C, the reaction is kept warm for 2-3h, the temperature is naturally lowered to room temperature, and post-processed to obtain the composite chitosan.
[0014] The synthesis reaction formula of composite chitosan is:
[0015]
[0016] Where: ;
[0017] To activate chitosan.
[0018] The synthesis reaction mechanism of composite chitosan is:
[0019] During the reaction, the nitrile group on the 3-amino-4-hydroxybutyronitrile molecule is hydrolyzed in an aqueous ammonium chloride solution to form ammonium carboxylate. Then, the amino group on the 3-amino-4-hydroxybutyronitrile or activated chitosan molecule modified with ammonium carboxylate undergoes a nucleophilic addition reaction with formaldehyde to form a hydroxyl modification on the molecule. Aluminum chloride is then used as a catalyst to catalyze the dehydration condensation of the reaction product of the ammonium carboxylate-modified 3-amino-4-hydroxybutyronitrile, activated chitosan and formaldehyde to obtain a composite chitosan.
[0020] Furthermore, the dosage ratio of the 3-amino-4-hydroxybutyronitrile, activated chitosan and ammonium chloride solution is 2-3g:5-7g:15-20mL, the ammonium chloride solution is composed of ammonium chloride and purified water at a ratio of 1g:3mL, the mass concentration of the formaldehyde solution is 22-30%, and the molar ratio of formaldehyde, aluminum chloride and 3-amino-4-hydroxybutyronitrile is 2:0.1:1. The post-treatment includes: after the reaction is completed, the reaction system is kept at 70-80°C, and low-boiling substances are removed under reduced pressure to obtain composite chitosan.
[0021] Furthermore, the preparation method of activated chitosan is: chitosan and acetic acid solution are mixed, stirred until the system is dissolved, the temperature of the reaction system is increased to 40-48°C, hydrogen peroxide is added to the reaction system, and the system is stirred for 3-5 hours under warm condition, and post-processed to obtain activated chitosan.
[0022] The synthetic reaction mechanism of activated chitosan is:
[0023] During the reaction, the action of hydrogen peroxide under acidic conditions triggers the oxidative degradation of chitosan in a heated environment, resulting in the breakage of the chitosan molecular chain to generate low-molecular-weight chitosan, which is then separated and precipitated from the solution by ethanol as a poor solvent to prepare activated chitosan.
[0024] Furthermore, the amount ratio of the chitosan, acetic acid solution and hydrogen peroxide is 1g:8-10mL:2-3mL, the deacetylation degree of the chitosan is 85-95%, the mass concentration of the acetic acid solution is 3-5wt%, and the mass concentration of the hydrogen peroxide is 20-25%. The post-treatment includes: after the reaction is completed, adding anhydrous ethanol to the reaction system, stirring at a temperature of 20-30min, filtering, washing the filter cake with 80-90wt% ethanol aqueous solution for 3 times and then drying, transferring the filter cake to a drying oven at a temperature of 50-60°C, and vacuum drying to constant weight to obtain activated chitosan.
[0025] Furthermore, the preparation method of the ferric chloride solution is: mixing ferrous chloride and hydrochloric acid solution, adding sodium hypochlorite solution to the reaction system at room temperature, and keeping the temperature for 6-8 hours to obtain the ferric chloride solution.
[0026] The synthetic reaction mechanism of ferric chloride solution is:
[0027] 2Fe 2+ +ClO − +2H + →2Fe 3+ +Cl − +H2O
[0028] Fe 3+ +H2O→Fe(OH) 2+ +H +
[0029] 2Fe(OH) 2+ →Fe2(OH)2 4+
[0030] 2Fe(OH) 2+ →Fe2(OH)2 4+
[0031] 3Fe(OH) 2+ →Fe3(OH)4 5+ +H +
[0032] 3Fe(OH) 2+ →Fe3(OH)4 5+ +H +
[0033] Fe2(OH)2 4+ +4Cl − →Fe2(OH)2Cl4
[0034] Fe3(OH)4 5+ +5Cl − →Fe3(OH)4Cl5
[0035] The synthetic reaction mechanism of ferric chloride solution is:
[0036] During the reaction, sodium hypochlorite is used as an oxidant. When sodium hypochlorite is in a mixed solution of ferrous chloride and hydrochloric acid, the hypochlorite ions oxidize the ferrous ions to form ferric ions. The generated trivalent iron ions are further polymerized to form polynuclear hydroxy-iron complexes. The polynuclear hydroxy-iron complexes combine with Cl⁻ to form polyferric chloride to obtain a ferric chloride solution.
[0037] Furthermore, the dosage ratio of the ferrous chloride, the hydrochloric acid solution and the sodium hypochlorite solution is 3g:2g:1g, the concentration of the hydrochloric acid solution is 6-8mol / L, and the sodium hypochlorite solution is composed of sodium hypochlorite and deionized water at a ratio of 1g:1mL.
[0038] The invention discloses a method for preparing a composite decolorizing agent for industrial wastewater. The method comprises the following steps: uniformly mixing composite polyolefin, ferric chloride solution and polyacrylamide to obtain the composite decolorizing agent.
[0039] The present invention has the following beneficial effects:
[0040] 1. The composite decolorant for industrial wastewater of the present invention uses chitosan with a high degree of deacetylation as a raw material, activates it, generates oligomeric chitosan and exposes more free amino groups and hydroxyl groups, and reacts formaldehyde with the amino groups of the activated chitosan and the amino groups of 3-amino-4-hydroxybutyronitrile to generate a hydroxymethyl intermediate, which is then dehydrated and condensed to form a stable -CH2-NH- cross-linking bond, forming a three-dimensional cross-linking structure, increasing the rigidity of the molecular chain while introducing more amino groups and hydroxyl groups, strengthening the cationicity, and enhancing the electrostatic adsorption of anionic dyes, further enhancing the color substances in printing and dyeing wastewater. In addition to serving as a catalyst, aluminum chloride has excellent adsorption capacity. The aluminum ions in its molecules form Al-O or Al-N coordination bonds with the hydroxyl or amino groups of chitosan to build a stable three-dimensional cross-linked network, increase the specific surface area and porosity, and capture macromolecular dyes through physical interception. The three-dimensional cross-linked structure of the composite chitosan molecules removes soluble organic matter in wastewater through pore interception and surface adsorption, thereby reducing COD. Aluminum ions form aluminum hydroxide colloid in aqueous solution, which efficiently removes colloidal and small molecular organic matter through the dual mechanism of "adsorption-netting", further reducing the COD of industrial wastewater.
[0041] 2. In the composite decolorizing agent for industrial wastewater of the present invention, acryloyloxyethyl trimethyl ammonium chloride and fumaric acid form a polyolefin coating on the composite chitosan through free radical polymerization reaction. The quaternary amino groups on the acryloyloxyethyl trimethyl ammonium chloride molecules destroy the colloid stability through charge neutralization, promote the flocculation and sedimentation of organic matter, and improve the COD removal rate. In addition, the quaternary amino group provides positive charge for the composite polyolefin molecules, and electrostatically adsorbs the anionic dyes in the printing and dyeing industrial wastewater, thereby effectively removing the dyes and improving the decolorization rate. The polyolefin coating layer on the outside of the composite chitosan enhances the stability of the material in the wastewater and avoids the performance degradation caused by the dissolution of chitosan under acidic conditions.
[0042] 3. The composite decolorizing agent for industrial wastewater of the present invention is prepared by preparing a ferric chloride solution of a polynuclear hydroxy-iron complex, which has a high-density positive charge. The negatively charged dye colloid particles are neutralized by electrostatic action, thereby destroying their stability and promoting flocculation and sedimentation of dye molecules. The polyferric chloride formed by the combination of Cl⁻ and the polynuclear complex captures dye molecules by surface adsorption and net capture. The quaternary amino groups in the composite polyolefin provide a high-density positive charge, further strengthening the charge neutralization effect, forming a stronger charge neutralization ability, and significantly improving the decolorization rate of anionic dyes. In addition, the multinuclear complex structure of the ferric chloride solution and polyacrylamide cooperate with each other to further promote the flocculation and sedimentation of organic matter, thereby significantly improving the decolorization rate and COD removal rate. DETAILED DESCRIPTION
[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The deacetylation degree of the chitosan used in the present invention is 85-95%.
[0045] Example 1
[0046] This embodiment provides a method for preparing a composite decolorizing agent for industrial wastewater, comprising the following steps:
[0047] S1. Preparation of activated chitosan
[0048] Weigh: 30 g of chitosan and 240 mL of 3 wt% acetic acid solution, add into a three-necked flask and stir until the system is dissolved. The temperature of the three-necked flask is raised to 40°C. 60 mL of 20 wt% hydrogen peroxide is added into the three-necked flask, and the mixture is stirred for 3 h. 900 mL of anhydrous ethanol is added into the three-necked flask, and the mixture is stirred for 20 min. The filter cake is washed three times with 80 wt% ethanol aqueous solution and then dried. The filter cake is transferred into a drying oven at 50°C. The drying oven is evacuated to a vacuum degree of 80 pa, and the mixture is dried under vacuum to a constant weight to obtain activated chitosan.
[0049] S2. Preparation of composite chitosan
[0050] Weigh: 8 g of 3-amino-4-hydroxybutyronitrile, 20 g of activated chitosan, and 60 mL of ammonium chloride solution, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 28 ° C, add 22 wt% formaldehyde solution containing 0.160 mol of formaldehyde into the three-necked flask, avoid reaction temperature rise during dropwise addition, and control the reaction temperature not higher than 65 ° C. After the dropwise addition is completed, add 1.1 g of aluminum chloride into the three-necked flask, stir and dissolve, raise the temperature of the three-necked flask to 70 ° C, keep the reaction for 2 hours, cool naturally to room temperature, keep the three-necked flask at 70 ° C, evacuate the three-necked flask to a vacuum degree of 30 Pa, and remove low-boiling substances under reduced pressure to obtain composite chitosan.
[0051] S3. Preparation of composite polyolefins
[0052] Azobisisobutyronitrile and deionized water were mixed evenly at a ratio of 1 g:10 mL to obtain an initiator solution for later use;
[0053] Weigh: 28 g of composite chitosan, 35 g of acryloyloxyethyltrimethylammonium chloride, 14 g of fumaric acid, and 210 mL of deionized water, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 70° C., add 35 mL of initiator solution dropwise into the three-necked flask, and keep warm for 5 hours to obtain a composite polyolefin.
[0054] S4. Preparation of ferric chloride solution
[0055] Mix sodium hypochlorite and deionized water at a ratio of 1 g:1 mL to obtain a sodium hypochlorite solution for later use;
[0056] Weigh: 30 g of ferrous chloride and 20 g of 6 mol / L hydrochloric acid solution, add into a beaker and stir; at room temperature, add 10 g of sodium hypochlorite solution into the beaker, and keep warm for 6 h to obtain a ferric chloride solution.
[0057] S5. Preparation of composite decolorizing agent
[0058] Weigh by weight: 70 parts of composite polyolefin, 25 parts of ferric chloride solution and 3 parts of polyacrylamide, add them into a three-necked flask and stir evenly, raise the temperature of the three-necked flask to 70°C, evacuate the three-necked flask to a vacuum degree of 30 Pa, and evaporate low-boiling substances under reduced pressure to obtain a composite decolorizer.
[0059] Example 2
[0060] This embodiment provides a method for preparing a composite decolorizing agent for industrial wastewater, comprising the following steps:
[0061] S1. Preparation of activated chitosan
[0062] Weigh: 30 g of chitosan and 270 mL of 4 wt% acetic acid solution, add into a three-necked flask and stir until the system is dissolved. The temperature of the three-necked flask is raised to 44°C. 75 mL of 23 wt% hydrogen peroxide is added into the three-necked flask, and the mixture is stirred for 4 h. 900 mL of anhydrous ethanol is added into the three-necked flask, and the mixture is stirred for 25 min. The filter cake is washed three times with 85 wt% ethanol aqueous solution and then dried. The filter cake is transferred into a drying oven at a temperature of 55°C. The drying oven is evacuated to a vacuum degree of 90 pa, and the mixture is dried under vacuum to a constant weight to obtain activated chitosan.
[0063] S2. Preparation of composite chitosan
[0064] Weigh: 10 g of 3-amino-4-hydroxybutyronitrile, 24 g of activated chitosan, and 70 mL of ammonium chloride solution, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 30 ° C, add 26 wt% formaldehyde solution containing 0.200 mol of formaldehyde into the three-necked flask, avoid reaction temperature rise during dropwise addition, and control the reaction temperature not higher than 65 ° C. After the dropwise addition is completed, 1.3 g of aluminum chloride is added to the three-necked flask, stirred and dissolved, and the temperature of the three-necked flask is raised to 75 ° C. The reaction is kept warm for 2.5 hours, and the temperature is naturally lowered to room temperature. The three-necked flask is kept at 75 ° C. The three-necked flask is evacuated to a vacuum degree of 40 Pa, and low-boiling substances are removed under reduced pressure to obtain composite chitosan.
[0065] S3. Preparation of composite polyolefins
[0066] Azobisisobutyronitrile and deionized water were mixed evenly at a ratio of 1 g:10 mL to obtain an initiator solution for later use;
[0067] Weigh: 28 g of composite chitosan, 35 g of acryloyloxyethyltrimethylammonium chloride, 14 g of fumaric acid, and 210 mL of deionized water, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 75° C., add 35 mL of initiator solution dropwise into the three-necked flask, and keep warm for reaction for 5.5 h to obtain a composite polyolefin.
[0068] S4. Preparation of ferric chloride solution
[0069] Mix sodium hypochlorite and deionized water at a ratio of 1 g:1 mL to obtain a sodium hypochlorite solution for later use;
[0070] Weigh: 30 g of ferrous chloride and 20 g of 7 mol / L hydrochloric acid solution, add into a beaker and stir; at room temperature, add 10 g of sodium hypochlorite solution into the beaker, and keep warm for 7 h to obtain a ferric chloride solution.
[0071] S5. Preparation of composite decolorizing agent
[0072] Weigh by weight: 75 parts of composite polyolefin, 27 parts of ferric chloride solution, and 4 parts of polyacrylamide, add them into a three-necked flask and stir evenly, raise the temperature of the three-necked flask to 75°C, evacuate the three-necked flask to a vacuum degree of 40 Pa, and evaporate low-boiling substances under reduced pressure to obtain a composite decolorizer.
[0073] Example 3
[0074] This embodiment provides a method for preparing a composite decolorizing agent for industrial wastewater, comprising the following steps:
[0075] S1. Preparation of activated chitosan
[0076] Weigh: 30 g of chitosan and 300 mL of 5 wt% acetic acid solution, add into a three-necked flask and stir until the system is dissolved. The temperature of the three-necked flask is raised to 48°C. 90 mL of 25 wt% hydrogen peroxide is added into the three-necked flask, and the mixture is stirred for 5 h. 900 mL of anhydrous ethanol is added into the three-necked flask, and the mixture is stirred for 30 min. The filter cake is washed three times with 90 wt% ethanol aqueous solution and then dried. The filter cake is transferred into a drying oven at 60°C. The drying oven is evacuated to a vacuum degree of 100 Pa, and the mixture is dried under vacuum to a constant weight to obtain activated chitosan.
[0077] S2. Preparation of composite chitosan
[0078] Weigh: 12 g of 3-amino-4-hydroxybutyronitrile, 28 g of activated chitosan, and 80 mL of ammonium chloride solution, add them into a three-necked flask and stir, raise the temperature of the three-necked flask to 32 ° C, add 30 wt% formaldehyde solution containing 0.240 mol of formaldehyde into the three-necked flask, avoid reaction temperature rise during dropwise addition, and control the reaction temperature not higher than 65 ° C. After the dropwise addition is completed, add 1.6 g of aluminum chloride into the three-necked flask, stir and dissolve, raise the temperature of the three-necked flask to 80 ° C, keep the reaction for 3 hours, cool naturally to room temperature, keep the three-necked flask at 80 ° C, evacuate the three-necked flask to a vacuum degree of 50 Pa, and remove low-boiling substances under reduced pressure to obtain composite chitosan.
[0079] S3. Preparation of composite polyolefins
[0080] Azobisisobutyronitrile and deionized water were mixed evenly at a ratio of 1 g:10 mL to obtain an initiator solution for later use;
[0081] Weigh: 28 g of composite chitosan, 35 g of acryloyloxyethyltrimethylammonium chloride, 14 g of fumaric acid, and 210 mL of deionized water, add into a three-necked flask and stir, raise the temperature of the three-necked flask to 80° C., add 35 mL of initiator solution dropwise into the three-necked flask, and keep warm for 6 hours to obtain a composite polyolefin.
[0082] S4. Preparation of ferric chloride solution
[0083] Mix sodium hypochlorite and deionized water at a ratio of 1 g:1 mL to obtain a sodium hypochlorite solution for later use;
[0084] Weigh: 30 g of ferrous chloride and 20 g of 8 mol / L hydrochloric acid solution, add into a beaker and stir; at room temperature, add 10 g of sodium hypochlorite solution into the beaker, and keep warm for 8 h to obtain a ferric chloride solution.
[0085] S5. Preparation of composite decolorizing agent
[0086] Weigh by weight: 80 parts of composite polyolefin, 30 parts of ferric chloride solution, and 5 parts of polyacrylamide, add them into a three-necked flask and stir evenly, raise the temperature of the three-necked flask to 80°C, evacuate the three-necked flask to a vacuum degree of 50 Pa, and evaporate low-boiling substances under reduced pressure to obtain a composite decolorizer.
[0087] Comparative Example 1
[0088] The difference between this comparative example and Example 3 is that step S1 is eliminated, and the activated chitosan in step S2 is replaced by the chitosan in step S1.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 3 is that step S3 is eliminated, and the composite chitosan in step S2 replaces the composite polyolefin in step S5.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 3 is that step S4 is eliminated and no ferric chloride solution is added in step S5.
[0093] Performance Testing:
[0094] The composite decolorizing agent prepared in Examples 1-3 and Comparative Examples 1-3 was added to industrial printing and dyeing wastewater at an addition amount of 100 mg / L, and the mixture was stirred for decolorization for 30 minutes, and allowed to stand for 30 minutes. The supernatant was taken to obtain decolorized wastewater. The decolorization rate of the sample was determined according to Formula 1, and the COD removal rate of the sample was tested according to Formula 2.
[0095] Formula 1: , where A1 is the absorbance of the decolorizing wastewater after dilution 10 times, and A0 is the absorbance of the industrial printing and dyeing wastewater after dilution 10 times;
[0096] Formula 2: , where COD1 is the COD value of decolorization wastewater, COD0 is the COD value of industrial printing and dyeing wastewater. The specific test results are shown in Table 1 below.
[0097] Table 1-Performance test data of the sample
[0098] Data Analysis: A comparative analysis of the data in Table 1 above shows that the composite decolorizing agent prepared by the present invention has a decolorization rate of 95.6% for industrial printing and dyeing wastewater treatment, and a COD removal rate of 85.1%. All performance test data are better than those of the comparative example. The composite chitosan having a multidimensional cross-linked structure is prepared by activating chitosan, and the composite chitosan is modified with acryloyloxyethyltrimethylammonium chloride and fumaric acid to prepare a composite polyolefin, and the composite polyolefin is enhanced with ferric chloride solution and polyacrylamide to prepare a composite decolorizing agent, which not only effectively improves the decolorization rate of the composite decolorizing agent for printing and dyeing industrial wastewater, but also improves its COD removal rate for printing and dyeing industrial wastewater.
[0099] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A composite decolorizing agent for industrial wastewater, characterized in that: The invention comprises the following components in parts by weight: 70-80 parts of composite polyolefin, 25-30 parts of ferric chloride solution, and 3-5 parts of polyacrylamide; The preparation method of the composite polyolefin is as follows: composite chitosan, acryloyloxyethyl trimethyl ammonium chloride, fumaric acid and deionized water are mixed, the temperature of the reaction system is increased to 70-80° C., an initiator solution is added dropwise to the reaction system, and the reaction is carried out by heat preservation for 5-6 hours to obtain the composite polyolefin.
2. A composite decolorizing agent for industrial wastewater according to claim 1, characterized in that: The amount ratio of the composite chitosan, acryloyloxyethyltrimethylammonium chloride, fumaric acid, deionized water and initiator solution is 4g:5g:2g:30mL:5mL, and the initiator solution is composed of azobisisobutyronitrile and deionized water in a ratio of 1g:10mL.
3. A composite decolorizing agent for industrial wastewater according to claim 1, characterized in that: The preparation method of the composite chitosan comprises the following steps: 3-amino-4-hydroxybutyronitrile, activated chitosan and ammonium chloride solution are mixed and stirred, the temperature of the reaction system is raised to 28-32° C., formaldehyde solution is added dropwise to the reaction system, the reaction temperature is controlled not to be higher than 65° C., after the addition is completed, aluminum chloride is added to the reaction system, the temperature of the reaction system is raised to 70-80° C., the reaction is kept warm for 2-3 hours, the temperature is naturally lowered to room temperature, and post-processed to obtain the composite chitosan.
4. A composite decolorizing agent for industrial wastewater according to claim 3, characterized in that: The dosage ratio of the 3-amino-4-hydroxybutyronitrile, activated chitosan and ammonium chloride solution is 2-3g:5-7g:15-20mL, the ammonium chloride solution is composed of ammonium chloride and purified water at a ratio of 1g:3mL, the mass concentration of the formaldehyde solution is 22-30%, and the molar ratio of formaldehyde, aluminum chloride and 3-amino-4-hydroxybutyronitrile is 2:0.1:
1. The post-treatment comprises: after the reaction is completed, the reaction system is kept at 70-80°C, and low-boiling substances are evaporated under reduced pressure to obtain composite chitosan.
5. A composite decolorizing agent for industrial wastewater according to claim 3, characterized in that: The preparation method of activated chitosan is as follows: chitosan and acetic acid solution are mixed, stirred until the system is dissolved, the temperature of the reaction system is increased to 40-48°C, hydrogen peroxide is added to the reaction system, the system is stirred for 3-5 hours, and post-processed to obtain activated chitosan.
6. A composite decolorizing agent for industrial wastewater according to claim 5, characterized in that: The amount ratio of the chitosan, acetic acid solution and hydrogen peroxide is 1g:8-10mL:2-3mL, the deacetylation degree of the chitosan is 85-95%, the mass concentration of the acetic acid solution is 3-5wt%, and the mass concentration of the hydrogen peroxide is 20-25%. The post-treatment comprises: after the reaction is completed, adding anhydrous ethanol to the reaction system, stirring at a temperature of 20-30min, filtering, washing the filter cake with 80-90wt% ethanol aqueous solution for 3 times and then drying, transferring the filter cake to a drying oven at a temperature of 50-60°C, and vacuum drying to constant weight to obtain activated chitosan.
7. A composite decolorizing agent for industrial wastewater according to claim 1, characterized in that: The preparation method of the ferric chloride solution is as follows: ferrous chloride and hydrochloric acid solution are mixed and stirred, sodium hypochlorite solution is added to the reaction system at room temperature, and the reaction is carried out by heat preservation for 6-8 hours to obtain the ferric chloride solution.
8. A composite decolorizing agent for industrial wastewater according to claim 7, characterized in that: The dosage ratio of the ferrous chloride, hydrochloric acid solution and sodium hypochlorite solution is 3g:2g:1g, the concentration of the hydrochloric acid solution is 6-8mol / L, and the sodium hypochlorite solution is composed of sodium hypochlorite and deionized water at 1g:1mL.
9. A method for preparing a composite decolorizing agent for industrial wastewater according to any one of claims 1 to 8, characterized in that: The preparation method of the composite decolorizing agent for industrial wastewater comprises the following steps: uniformly mixing composite polyolefin, ferric chloride solution and polyacrylamide to obtain the composite decolorizing agent.
Citation Information
Patent Citations
High-efficiency decolorizing treatment agent for industrial waste water and preparation method thereof
CN101596444A